SURVEY OF PHYSICAL FITNESS LEVELS OF CLASS V AND VI STUDENTS OF JATIBATUR I STATE PRIMARY SCHOOL - kurniawan, Kukuh Yusuf (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This research was motivated by the absence of data on the level of physical fitness of students at SD Negeri Jatibatur 1, Gemolong District, Sragen Regency. So this research aims to determine the level of physical fitness of students at SD Negeri Jatibatur 1, Gemolong District, Sragen Regency. The subjects in this research were 28 students in grades V and VI, consisting of 14 male students and 14 female students. The research method used in this research is a test survey method, using the Indonesian physical fitness test instrument. The Indonesian physical fitness test (TKJI) includes a 40 meter sprint, hanging bent elbows, lying down for 30 seconds, jumping upright and a long run of 600 meters. The data analysis technique in this research uses standard physical fitness norms from TKJI to measure students' physical fitness levels. The results of this study obtained a classification for the level of physical fitness of students class V and VI, most of which were in the medium category, 14 children (50%), the poor category, 9 children (32.1%), the good category, 4 children (14.3%), the 1 child (3.6%) is very poor, and 0 children (0%) are in the very good category. The conclusion of this research is that the level of physical fitness in class V and VI students at SD Negeri Jatibatur 1, Gemolong District, Sragen Regency is in the medium category. The researcher's suggestions for physical education teachers and schools are to improve and implement programs oriented towards fostering and improving students' physical fitness.